Taxonomic assessment of the inquiline fauna (Hymenoptera: Cynipidae: Synergini, Ceroptresini) reared from cynipid galls on oaks (Quercus spp.) from South Korea - Lobato-Vila, Irene; Kang, Minjoon; Roca-Cusachs, Marcos; Kim, Ilkwon; Jung, Sunghoon; Pujade-Villar, Juli (Zootaxa, 2020)
A complete taxonomic assessment of the inquiline fauna (Hymenoptera: Cynipidae: Synergini, Ceroptresini) reared from cynipid oak galls collected in South Korea is conducted for the first time. Previously, six species were known from this country (Ceroptres kovalevi Belizin, 1973; Synergus chinensis Melika, Ács & Bechtold, 2004; Synergus japonicus Walker, 1874; Ufo koreanus Melika, Pujade-Villar & Choi, 2007; and presumably, Saphonecrus chaodongzhui Melika, Ács & Bechtold, 2004 and Ufo cerroneuroteri Tang & Melika, 2012). The study of new material reared from cynipid galls collected from oaks (Quercus spp.) from various locations throughout South Korea has increased the total number of inquiline species known from this country to 14, of which seven are new country records (Saphonecrus shirakashii (Shinji, 1940); Sa. symbioticus Melika & Schwéger, 2015; Synergus abei Melika & Schwéger, 2015; S. belizinellus Schwéger & Melika 2015; S. formosanus Schwéger & Melika, 2015; S. ishikarii Melika & Schwéger, 2015; and S. symbioticus Schwéger & Melika, 2015), and one is a new species: Synergus minutus Lobato-Vila & Pujade-Villar, sp. nov. The new species is formally described and illustrated. New biological and distribution data are provided for both the newly recorded species and the other reared species. The Korean fauna is compared with that from other countries within the Eastern Palearctic and the Oriental regions.